Trabalho e família: um estudo da interação de papéis com secretários executivos - Maia, Kadma Lanubia da Silva (2012)
The balance between the demands of two important spheres of human life, work and family, has become a challenge due to the pressures of the contemporary that is expanding around the difficulties of reconciling these two comínios. In this sense, this research aimed to understand the work-family interaction in the perception of executive secretaries. The analysis approach used was qualitative research, by worrying about a reality that can not be quantified due to the subjectivity of his goal. The data collection technique used was the semistructured interview to twenty executive secretaries, servants of a Federal Institution of Higher Education. For the understanding and interpretation of the data, we used the technique of content analysis. The results of both analyzes identified the existence of conflict as enrichment in this interaction. The time was identified as the largest generator of conflict work. The overload, relationship stress and conflict emerged as elements common to both domains. As main implications of labor disputes, were revealed: problamas health for secretaries and stress. As main implications of family conflicts emerged: motivation for work, lower performance and lack of concentration. The attempt at balance was identified as the strategy most used by secretaries to minimize work-family conflict. The work-family enrichment was seen as resources that contribute to improving the lives of the secretary in both domains. The opportunity to add knowledge was highlighted as enriching element of work and family values ​​as elements enriching family. The support and experience emerged as enrichment items common to both domains. Regarding the implications of enrichment resulting from the interaction of work and family, the more perceived by respondents were: increased knowledge and skills, material and psychological benefits, improved quality of life and personal and professional fulfillment. From the perception of executive secretaries, work and family spheres of human life are essential and complementary, and that help is contrary, however, this relationship is the primary management of conflicts, ie, how the individual sees and manages the negative side of the work-family